STRUCTURAL FEATURES OF SQUAMOUS CELL CARCINOMAS IN PATIENTS WITH LUNG CANCER WITH PARANEOPLASTIC RHEUMATIC SYNDROME - Lysenko, S.A.; Bolyukh B.А.; Strizhalkovsky О.V. (World of Medicine and Biology, 2012)
Microscopically examined 105 cases of squamous cell carcinomas in patients with lung cancer: 29 – patients with rheumatic paraneoplastic syndrome (PNS) and 76 – without rheumatic paraneoplastic syndrome. Morphologically: In patients with primary squamous cell carcinoma of the lung with rheumatic PNS, a more pronounced sclerotic process was noted in the parenchyma along with a weak development of necrotic changes in tumors. This was confirmed by a significant increase of specific weight of connective tissue (p